2013
DOI: 10.1017/s0959270913000129
|View full text |Cite
|
Sign up to set email alerts
|

Crop vegetation structure is more important than crop type in determining where Lesser Kestrels forage

Abstract: Summary 21We studied foraging habitat selection by Lesser Kestrels throughout the breeding period 22 in South-Western Spain by means of transects in which foraging observations were 23 recorded. We focused on the effect of habitat and crop type, but also on the effect of 24 vegetation structure and the presence of agricultural activities in the field on Lesser 25Kestrel's use. We considered both the accumulated use of the foraging area during the 26 breeding season and the instantaneous foraging habitat select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 35 publications
3
22
0
Order By: Relevance
“…Cereals have little demand for pesticides and are, mostly, nonirrigated in Greece (EEC 2007). The results agree with the findings of other lesser kestrel studies in the Iberian Peninsula where the species occurrence is associated with extensive cereals, a habitat related with the abundance of preferred prey, mainly during chick-rearing period that is crucial for the species reproductive success (Doňazar et al 1993;Parr et al 1995;Bustamante 1997;Tella et al 1998;Rodríguez et al 2006;De Frutos & Olea 2008;Catry et al 2013;Rodríguez et al 2014;Hernán-dez-Pliego et al 2017). Thus, Lesser Kestrels could stand as a biodiversity surrogate and as an umbrella species for delivering farmland biodiversity conservation in the agro-ecosystems of Greece.…”
Section: Lesser Kestrel Colonies -Habitat Associationssupporting
confidence: 90%
See 3 more Smart Citations
“…Cereals have little demand for pesticides and are, mostly, nonirrigated in Greece (EEC 2007). The results agree with the findings of other lesser kestrel studies in the Iberian Peninsula where the species occurrence is associated with extensive cereals, a habitat related with the abundance of preferred prey, mainly during chick-rearing period that is crucial for the species reproductive success (Doňazar et al 1993;Parr et al 1995;Bustamante 1997;Tella et al 1998;Rodríguez et al 2006;De Frutos & Olea 2008;Catry et al 2013;Rodríguez et al 2014;Hernán-dez-Pliego et al 2017). Thus, Lesser Kestrels could stand as a biodiversity surrogate and as an umbrella species for delivering farmland biodiversity conservation in the agro-ecosystems of Greece.…”
Section: Lesser Kestrel Colonies -Habitat Associationssupporting
confidence: 90%
“…Field margins were not included in model development, because they could not be detected by the image classification analysis because of the coarseness of the thematic map resolution (30 m pixel). This habitat is commonly reported to be preferred for foraging by Lesser Kestrels (Parr et al 1997;Tella et al 1998;Rodríguez et al 2006;Rodríguez & Bustamante 2008;Rodríguez et al 2014).…”
Section: Lesser Kestrel Colonies -Habitat Associationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[12,57]. In diet analyses studies, Orthoptera were identified as lesser kestrel's most favourable prey items [16,17].…”
Section: Foraging Habitat Selection Of Lesser Kestrelsmentioning
confidence: 99%